2011
DOI: 10.1063/1.3623471
|View full text |Cite
|
Sign up to set email alerts
|

Reverse nonequilibrium molecular dynamics simulation of thermal conductivity in nanoconfined polyamide-6,6

Abstract: A new molecular dynamics simulation method, with coupling to external baths, is used to perform equilibrium simulations on polyamide-6,6 trimers nanoconfined between graphene surfaces, in equilibrium with the bulk polymer. The method is coupled with the reverse nonequilibrium molecular dynamics simulation technique to exchange heat in the direction normal to the surfaces. To be able to study the effect of confinement on the heat conductance in nanoconfined pores, in this work a number of simulations on systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 57 publications
6
30
0
Order By: Relevance
“…In a previous study we have employed this method to study the heat transfer across the pore. 22 Our results indicated that a substantial temperature drop is observed at the interface. Resultantly, the coefficient of thermal conductivity in the perpendicular direction, depending on the pore width, is shown to be smaller than the corresponding bulk value.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…In a previous study we have employed this method to study the heat transfer across the pore. 22 Our results indicated that a substantial temperature drop is observed at the interface. Resultantly, the coefficient of thermal conductivity in the perpendicular direction, depending on the pore width, is shown to be smaller than the corresponding bulk value.…”
Section: Methodsmentioning
confidence: 85%
“…[20][21][22] We have shown that the heat flow across the pore occurs much slower than that in the bulk polymer. 22 In this work we will examine the heat flow in the direction parallel to the surfaces, by coupling our NAPT ensemble simulation method with the RNEMD technique [23][24][25] to study the anisotropic heat flow in naoconfined polymers. Same as the previous work, our polymeric system is a sample of polyamide-6,6 oligomers (the chemical structure is shown in Fig.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…This may be due to the ultralow thermal conductivity of the polymer (~0.1 W/m·K) compared to that of graphene (>100 W/m·K), transforming the ballistic heat transfer in graphene to the diffusive heat transfer in polymers [76,77]. Moreover, a number of theoretical studies have demonstrated that the interfacial thermal resistance (often known as the Kapitza resistance) between graphene and polymer also lowers the thermal conductivity of the composite films [78][79][80][81].…”
Section: Hybridization With Other Componentsmentioning
confidence: 99%